Receptor tyrosine kinase recepteur d'origine nantais as predictive marker for aggressive prostate cancer in African Americans. Issue 6 (11th March 2019) - Bedolla, Roble G.; Shah, Dimpy P.; Huang, Shih‐Bo; Reddick, Robert L.; Ghosh, Rita; Kumar, Addanki P.
Abstract: Published evidence shows a correlation between several molecular markers and prostate cancer (PCa) progression including in African Americans (AAs) who are disproportionately affected. Our early detection efforts led to the identification of elevated levels of antiapoptotic protein, c‐FLIP and its upstream regulatory factors such as androgen receptor (AR), recepteur d'origine nantais (RON), a receptor tyrosine kinase in human prostate tumors. The primary objective of this study was to explore whether these markers play a role in racial disparities using immunohistochemistry in prostatectomy samples from a cohort of AA, Hispanic Whites (HWs), and non‐Hispanic Whites (NHWs). Bivariable and multivariable logistic regression analyses were used to identify a statistical association between molecular markers, possible correlation with risk factors including race, obesity, prostate‐specific antigen (PSA) and disease aggressiveness. Further, changes in the levels and expression of these molecular markers were also evaluated using human PCa cell lines. We found significantly elevated levels of RON ( P = 0.0082), AR ( P = 0.0001), c‐FLIP ( P = 0.0071) in AAs compared with HWs or NHWs. Furthermore, a higher proportion of HW and NHWs had a high Gleason score (>6) but not PSA as compared to AAs ( P = 0.032). In summary, our findings suggest that PSA was important in predicting aggressive disease for the cohort overall; however, high levels of RON may play a role in predisposing AA men to develop aggressive disease. Future research is needed using large datasets to confirm these findings and to explore whether all or any of these markers could aid in race‐specific stratification of patients for treatment.